Sanitary conditions diagnosis in vulnerable communities in the City of Recife and its influence on Covid-19 cases - Silva, Gérsica Moraes Nogueira da; Menezes, Athos Farias; Sobral, Maria do Carmo (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
The Covid-19 pandemic calls into question deficiencies in current public policies and infrastructure of basic services to the population in large urban centers. From health systems, environmental sanitation and social protection, particularly for the low-income population, this opens the debate of the values and priorities at different scales. The research study area are subnormal settlements located in the neighborhoods of Pina and Brasília Teimosa in the Metropolitan Region of Recife. The aim was to assess the sanitary conditions in ZEIS, by conducting semi-structured interviews and assessing secondary data. Among the interviewees, only 56.3% said they had sanitary sewage collection and another 74.4% (n=1041) had access to water supply by Compesa, showing a significant deficit in the provision of basic services. With the pandemic, the necessary production of detailed empirical field data from the perspective of the peripheries faces great scientific challenges. Ensuring access to ideal sanitary conditions is a right for all and is related in an integrated way to multiple SDGs of the 2030 agenda. Demanding safe, adequate and affordable housing, and inclusive and sustainable urbanization, with capacity for planning and management of participatory, integrated and sustainable human settlements.